Pelatihan Legalitas Usaha dan Sertifikat Halal Keripik Ubi di Desa Sei Bluru - Harmayani, Harmayani; Siregar, Emiel Salim; Andriani, Dian Ayu; Apdilah, Dicky; Sinambela, Nur Isnaini; Sartika, Sartika (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
In Sei Beluru Village, Meranti District, there are still problems in understanding the legality of business permits and the importance of halal certification. Many micro, small and medium enterprises (MSMEs) in the village do not yet have official business legality and halal certification, which is one of the inhibiting factors in expanding the market and increasing consumer confidence. The process of registering business legality and halal certification is considered complicated and requires adequate knowledge and assistance. The method used in this community service activity is direct training and assistance to cassava chip entrepreneurs in Sei Bluru Village. The training includes socialization regarding the importance of business legality and halal certification, a guide to registration procedures and a simulation of the process of managing business permits and halal certification. Assistance is provided to assist participants in filling out forms, completing documents, and carrying out the application process independently. The purpose of this activity is to increase the understanding of entrepreneurs regarding the importance of business legality and halal certification and to assist them in the process of managing both aspects. After this activity is carried out, it is hoped that cassava chip entrepreneurs in Sei Bluru Village can increase the competitiveness of their products in the market, especially markets that prioritize product halalness and clear business legality.Keywords : business legality; halal certificate; training; cassava chips; UMKM Abstrak : Di Desa Sei Beluru Kecamatan Meranti masih mengalami masalah pemahaman mengenai legalitas izin usaha dan pentingnya sertifikasi halal.  Banyak usaha mikro kecil menengah (UMKM) di desa tersebut yang belum memiliki legalitas usaha resmi dan sertifikasi halal sehingga menjadi salah satu faktor penghambat dalam memperluas pasar dan meningkatkan kepercayaan konsumen. Proses pendaftaran legalitas usaha dan sertifikasi halal dianggap rumit dan memerlukan pengetahuan serta pendampingan yang memadai. Metode yang digunakan dalam kegiatan pengabdian masyarakat ini adalah pelatihan dan pendampingan secara langsung kepada para pelaku usaha keripik ubi di Desa Sei Bluru. Pelatihan meliputi sosialisasi mengenai pentingnya legalitas usaha dan sertifikasi halal, panduan tata cara pendaftaran serta simulasi proses pengurusan izin usaha dan sertifikasi halal. Pendampingan dilakukan untuk membantu peserta dalam mengisi formulir, melengkapi dokumen, dan melakukan proses pengajuan secara mandiri. Tujuan dari kegiatan ini adalah untuk meningkatkan pemahaman para pelaku usaha mengenai pentingnya legalitas usaha dan sertifikasi halal serta membantu mereka dalam proses pengurusan kedua aspek tersebut. Kata kunci: legalitas usaha; sertifikat halal; pelatihan; keripik ubi; UMKM